2006
DOI: 10.1557/jmr.2006.0167
|View full text |Cite
|
Sign up to set email alerts
|

Mg-doped Nd-Ba-Cu-O generic seed crystals for the top-seeded melt growth of large-grain (rare earth)-Ba-Cu-O bulk superconductors

Abstract: We report the fabrication of Mg-doped NdBCO generic seed crystals, which have been developed recently for the fabrication of any rare earth (RE) based (RE)-Ba-Cu-O single-grain superconductor, with a wide range of Nd 1+x Ba 2-x Cu 3-y Mg y O 7-␦ compositions. Three basic characteristics of the seed crystals required for effective seeding of bulk (RE)BCO materials were studied in detail. We report the chemical, crystallographic, microstructural, and superconducting properties of the seeds and demonstrate clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…This is important because the superconducting transition temperature (T c ) of Y-123 is particularly sensitive to the presence of impurities. 28 Elimination of carbon and the formation of a high purity of a superconducting phase on both micro-and macroscales is confirmed by Raman spectroscopy and X-ray diffraction (XRD). We then fabricate YBCO nanostructured powders (Y-211À30 nm and Y-123À12 nm, with T c ≈ 90.9 K) and a bulk sample using the nanostructured Y-211, with a ∼20% improvement in J c compared to a bulk sample prepared using commercial micrometer-sized powders.…”
mentioning
confidence: 95%
“…This is important because the superconducting transition temperature (T c ) of Y-123 is particularly sensitive to the presence of impurities. 28 Elimination of carbon and the formation of a high purity of a superconducting phase on both micro-and macroscales is confirmed by Raman spectroscopy and X-ray diffraction (XRD). We then fabricate YBCO nanostructured powders (Y-211À30 nm and Y-123À12 nm, with T c ≈ 90.9 K) and a bulk sample using the nanostructured Y-211, with a ∼20% improvement in J c compared to a bulk sample prepared using commercial micrometer-sized powders.…”
mentioning
confidence: 95%
“…Single-seeded and four-seeded Y-Ba-Cu-O (YBCO) bulk superconductors were fabricated by the TSMG technique using Mg-doped NdBCO generic seeds [26] from a precursor powder of composition 30 wt % of Y-211 + 70 wt % of Y-123 + 1 wt % of CeO 2 . The resultant powder mixture was pressed uniaxially (25 MPa) into a cylindrical pellet of diameter 25 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The single-seeded sample was grown using a cleaved Mg-doped NdBCO generic seed crystal placed at the centre of the pressed green pellet. The generic seed crystal was chosen for this application since it is known to have a significantly higher melting temperature than the composition of the target single grain and can hence overcome the problems of partial melting associated with seed crystal due to its potential contact with the liquid phase during processing [26]. Four seeds prepared as for the single-seeded sample were placed on the top surface of the green pellet.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is difficult to grow a large single domain SmBCO bulk superconductor with good superconducting properties without any dopant under atmospheric conditions. It has been reported that the development of MgO-NdBCO generic seed was used for fabricating REBCO bulk superconductors in the air using top-seeded melted texture growth (TSMTG) and top-seeded infiltration and growth (TSIG) processes [11,12]. It appears that the MgO-NdBCO generic seed has a higher melting temperature and similar crystal structure to all bulk superconductors in REBCO, although the difference in melting temperature between SmBCO precursor powders and the seed crystal is relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to avoid melting the NdBCO seed crystals during the growth of SmBCO bulk superconductors, two aspects should be considered. The first is to increase the melting temperature (T m ) of the NdBCO seed crystal to maintaining its thermal stability, which has been studied by several research groups [11,13,14]. The second is to enhance the heat dissipation of the solid phase rapidly and effectively to reduce the energy accumulation.…”
Section: Introductionmentioning
confidence: 99%